Characterization of neutralizing antibody with prophylactic and therapeutic efficacy against SARS-CoV-2 in rhesus monkeys - Shuang Wang (Nature Portfolio, 2020)
Here the authors characterize a monoclonal antibody from a COVID-19 convalescent patient that interferes with SARS-CoV-2 spike binding to ACE2 and has prophylactic and therapeutic activity in non-human primates. Antibody-dependent enhancement of infection is prevented by mutating the Fc region of the antibody.